(3EQTGO GddHjH Edi ebGUO MOjK GdMHjHs - (3CHh YHO Gddg eMeO Hf CMeO Hf eMeO Hf Ydj Hf ZGRi GdYKeGfj GdecfGSis; (3eSde Hf GdMLGL Hf eSde GdbTjQj GdfjSGHhQqi, CHh GdMSjf,J (B261 (3g` s
(3ChdgG (B:s
(3CeG HYO agPG cJGH SejJg EQTGO GddHjH Edi ebGUO MOjK GdMHjH s
(3BNQgG (B:s
(3heeG ai gPG GdMOjK ef CfhGY GdWHGb Hjf GdNajaJjf hGdKbjdJjf hjchf Hjf CSejf ced hGddg JYGdi GdeTchQ s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B221 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B232s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B62s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs